2018
DOI: 10.1038/s41598-018-31345-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion of PTH1–34 delayed fracture healing in mice

Abstract: Hyperparathyroidism, which is increased parathyroid hormone (PTH) levels in the blood, could cause delayed or non-union of bone fractures. But, no study has yet demonstrated the effects of excess continuous PTH exposure, such as that seen in hyperparathyroidism, for fracture healing. Continuous human PTH1–34 (teriparatide) infusion using an osmotic pump was performed for stabilized tibial fractures in eight-week-old male mice to determine the relative bone healing process compared with saline treatment. Radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Because bone is a target organ of PTH, continuously elevated serum PTH levels in PHPT patients likely affect bone fracture healing. A study showed that continuous teriparatide infusion to mice resulted in delayed healing of tibial fractures . Although the literature on fracture healing in PHPT patients is sparse, case reports may provide insight into the effect of PHPT on healing .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because bone is a target organ of PTH, continuously elevated serum PTH levels in PHPT patients likely affect bone fracture healing. A study showed that continuous teriparatide infusion to mice resulted in delayed healing of tibial fractures . Although the literature on fracture healing in PHPT patients is sparse, case reports may provide insight into the effect of PHPT on healing .…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that continuous teriparatide infusion to mice resulted in delayed healing of tibial fractures. (93) Although the literature on fracture healing in PHPT patients is sparse, case reports may provide insight into the effect of PHPT on healing. (94)(95)(96)(97)(98) Lancourt and Hochberg reported 4 fracture cases with delayed healing or nonunion in PHPT patients.…”
Section: Primary Hyperparathyroidism and Bone Fracture Healingmentioning
confidence: 99%
“…We detected pthr1a pth1ra expression uniformly in the developing ch (data not shown), but pth1rb may play a role in this asymmetry. Moreover, Parathyroid Hormone 1 (Pth1) acts like Pthlh in cartilage and can be carried in the bloodstream in rodents Development • Accepted manuscript (Jee et al, 2018;Yukata et al, 2018). Finally, pth4 is an ancestral Pth found in zebrafish but lost in eutherian mammals, that is expressed in the central nervous system, activates Pth1r receptors, and represses mineralization in the skeleton at long range (Suarez-Bregua et al, 2017).…”
Section: Pthlh Signaling Controls Spatial-temporal Patterns Of Embryonic Cartilage Hypertrophymentioning
confidence: 99%
“…This is termed as "anabolic index" of the drug. Teriparatide acts by promoting proliferation and differentiation of chondro as well as osteo-progenitor mesenchymal origin stem cells, maturation of chondrocytes, bone matrix protein production and formation of osteoclasts or osteoclastogenesis [10,11].…”
Section: Dudhia and Mahajanmentioning
confidence: 99%
“…Mishra et al in 2019 in their prospective study on use of teriparatide on delayed union of bone fracture demonstrated enhanced healing of fracture wound[9].Kim et al in 2019 in their study showed that teriparatide treatment caused significant increase in Harris Hip Score (p=0.02) and reduction in visual analogue pain scale score (p=0.0005). The mean post-operative time required for healing of fracture was found to decrease in patient treatment with teriparatide when compared to those who did not receive this therapy (i.e., 12.1 and 14.8 weeks, respectively)[10].Yukata et al in 2018 in their study showed that a continuous PTH 1-34 administration or infusion led to a delay in healing of a fracture wound due to delay in maturation of callus[11]. Saraf and Munot in 2017 demonstrated that fractures which were treated with 20 µg dosage of teriparatide demonstrated only signs of union associated with large amount of callus formation with significant reduction in radiographic union and early patient rehabilitation[12].…”
mentioning
confidence: 97%